2020
DOI: 10.1007/s41109-020-00271-5
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing reticulation in online social networks during disasters

Abstract: Online social network has become a new form of infrastructure for communities in spreading situational information in disasters. Developing effective interventions to improve the network performance of information diffusion is essential for people to rapidly retrieve information in coping with disasters and subsequent disruptions. Existing studies have investigated multiple aspects of online social networks in stationary situations and a separate manner. However, the networks are dynamic and different properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 47 publications
(48 reference statements)
0
8
0
Order By: Relevance
“…Yang et al 18 investigated influential Twitter users during Hurricane Harvey, highlighting the role of objective information sharing in disaster-related follower growth. Fan et al 13 studied dynamic changes in network structure during information diffusion of disaster information on social networks. Dong et al 19 created an information flow model from Weibo data to characterize information diffusion patterns during disasters.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Yang et al 18 investigated influential Twitter users during Hurricane Harvey, highlighting the role of objective information sharing in disaster-related follower growth. Fan et al 13 studied dynamic changes in network structure during information diffusion of disaster information on social networks. Dong et al 19 created an information flow model from Weibo data to characterize information diffusion patterns during disasters.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous studies have explored the evolution of disaster information on online social networks like Twitter and Facebook 12 , 13 , but little work exists for face-to-face networks or other offline communication methods. Our approach investigates the complex spread of information in disaster-affected communities by analyzing the interplay between five information sources: online social networks, local news, government sources, mainstream media, and print media.…”
Section: Introductionmentioning
confidence: 99%
“…When analyzing sentiment expressions on Twitter during Hurricane Harvey, Yuan et al [34] found that the impacted areas were more likely to indicate negative sentiment during disasters. Hence, the content of social media communications could shed insight on the dimension of human activities [35].…”
Section: A Community Realitymentioning
confidence: 99%
“…Hence, the content of social media communications could shed insight on the dimension of human activities. (Fan et al 2020c).…”
Section: Community Realitymentioning
confidence: 99%